Enhancing Online Consumer Trust And Sales Through Digital Tools: A Case Study on Shopee’s Haydan Healthy (International Journal of Scientific Research and Management (IJSRM), 2025)
The rise of digital commerce in the Industry 4.0 era has transformed consumer shopping behavior. In this context, e-commerce platforms such as Shopee have integrated tools like live streaming, vouchers, and enhanced user interfaces to improve consumer engagement and conversion rates. This study investigates the influence of live streaming, voucher promotions, and user experience on purchase decisions among Shopee users who purchased from the Haydan.Healthy store. A quantitative approach was applied using multiple linear regression with 100 purposively selected respondents. Results reveal that all three variables—live streaming, voucher, and user experience—positively and significantly impact consumer purchasing decisions. These findings offer strategic insight for online retailers in enhancing promotional efforts and improving digital experiences to drive sales. The study contributes to e-commerce literature by highlighting the importance of interactive and user-centric digital marketing strategies in influencing consumer behavior.